2006
DOI: 10.1103/physrevlett.97.046403
|View full text |Cite
|
Sign up to set email alerts
|

Can Correlations Drive a Band Insulator Metallic?

Abstract: We analyze the effects of the on-site Coulomb repulsion U on a band insulator using dynamical mean field theory (DMFT). We find the surprising result that the gap is suppressed to zero at a critical U c1 and remains zero within a metallic phase. At a larger U c2 there is a second transition from the metal to a Mott insulator, in which the gap increases with increasing U. These results are qualitatively different from Hartree-Fock theory which gives a monotonically decreasing but nonzero insulating gap for all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
182
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 14 publications
20
182
4
Order By: Relevance
“…In order to demonstrate our argument, we describe the effects of ∆ using the ionic Hubbard model [13,14,15,16,17,18,19] on the 2D honeycomb lattice. We examine the system using the coherent-potential approximation (CPA) [20], which is equivalent to the "scattering correction" of the Hubbard III approximation [21].…”
Section: Introductionmentioning
confidence: 99%
“…In order to demonstrate our argument, we describe the effects of ∆ using the ionic Hubbard model [13,14,15,16,17,18,19] on the 2D honeycomb lattice. We examine the system using the coherent-potential approximation (CPA) [20], which is equivalent to the "scattering correction" of the Hubbard III approximation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the evolution of a band insulator (BI) into a Mott insulator upon increasing the interaction strength has been studied in the context of the ionic Hubbard model, 5,6,7,8,9,10,11,12 a two-band Hubbard model with crystal-field splitting, 13 and a bilayer model with two identical Hubbard planes coupled by single-particle hopping. 14,15,16,17,18 Different scenarios have emerged with the possibility of an intervening phase and continuous or discontinuous transitions at critical interaction strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al found [6] that for the IHM, treated within single site DMFT, the band gap becomes zero at a critical U c1 , with a Mott gap re-emerging at a larger U c2 . In between, the system is metallic.…”
mentioning
confidence: 99%
“…This bears a strong resemblance to the dispersion relation of the 2D IHM whose superlattice potential ∆ j (−1) j n j similarly has the effect of opening a band gap at q = (π, π), altering the ∆ = 0 dispersion relation ǫ q to E q = ± ǫ 2 q + ∆ 2 . Real space Quantum Monte Carlo (QMC) [8] has supplemented DMFT studies of the IHM [6] by allowing for magnetic order and concluded that U could cause the appearance of a metallic phase. However, despite the similarity in E q between the IHM and Eq.…”
mentioning
confidence: 99%